Integrating family planning and VCT services in Ethiopia: Experiences of health care providers - Yoder, P. Stanley; Amare, Yared (DHS Qualitative Research Studies No. 14, 2008)
This study was undertaken primarily to understand what effect the efforts to integrate family planning and VCT services in health facilities had on health care providers' work and service delivery practices in two regions of Ethiopia: Oromia and Amhara. A secondary objective of the study was to identify what factors facilitated the integration of family planning services into existing VCT services in participating health facilities in these regions.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
This report presents the findings from a qualitative research study conducted in Ethiopia in 2007 as part of the MEASURE DHS project. Macro International Inc. coordinated this activity and provided technical assistance. Funding was provided by the United States Agency for International Development (USAID) under Contract No. GPO-C- 00-03-00002-00. The opinions expressed in this report are those of the authors and do not necessarily reflect the views of the Government of Ethiopia or USAID.